Stern review: the economics of climate change. Summary of the conclusions - Stern, Sir Nicholas (2007)
Scientific evidence is unquestionable today: climate change constitutes a serious global threat, which urgently demands an equally global response. This review has examined a wide range of data on the impact of climate change and its economic costs, having used various techniques to assess these costs and risks. Taking all this into account, the evidence collected in the review leads us to a clear conclusion: the benefits of taking prompt and firm measures will far exceed the economic costs of passivity.